A Decade of College Student Hunger: What We Know and Where We Need to Go - Rebecca L. Hagedorn-Hatfield; Lanae B. Hood; Adam Hege (Frontiers Media S.A., 2022)
The first article on college food insecurity, published in 2009, sparked conversation on the dark secret many students face while seeking a college degree; they do not have secure access to food. Over 10 years later, numerous investigators around the globe have reported on the heightened prevalence of college food insecurity, the correlates that increase risk, and the detrimental outcomes associated with not having a secure source of food. In this manuscript, we describe the decade of research devoted to college food insecurity and provide direction for research, programs, and policies moving forward. Replicable and valid data collection methods must be utilized, campus-based program evaluation implemented and disseminated, and evidence-based policies supported to achieve realistic goals of warding off hunger and food insecurity on college campuses as well as improve the lives of individuals after post-secondary education. Collectively, stakeholders on college campuses as well as off-campus advocates can be the catalyst to creating a nutritionally secure environment and it is imperative that food insecurity be prevented on college campuses to ensure college students are able to achieve degree attainment.